Comparison of cardiovascular biomarker expression in extracellular vesicles, plasma and carotid plaque for the prediction of MACE in CEA patients - Maarten C. Verwer; Joost Mekke; Nathalie Timmerman; Farahnaz Waissi; Arjan Boltjes; Gerard Pasterkamp; Gert J. de Borst; Dominique P. V. de Kleijn (Scientific Reports, 2023)
Abstract Extracellular vesicles (EV) are a novel biomarker source for diagnosis and prognosis of cardiovascular disease. A protein comparison of plasma EVs in relation to blood plasma and atherosclerotic plaque has not been performed but would provide insight into the origin and content of biomarker sources and their association with atherosclerotic progression. Using samples of 88 carotid endarterectomy patients in the Athero-Express, 92 proteins (Olink Cardiovascular III panel) were measured in citrate plasma, plasma derived LDL-EVs and atherosclerotic plaque. Proteins were correlated between sources and were related to pre-operative stroke and 3-year major adverse cardiovascular events (MACE). Plasma and EV proteins correlated moderately on average, but with substantial variability. Both showed little correlation with plaque, suggesting that these circulating biomarkers may not originate from the latter. Plaque (n = 17) contained most differentially-expressed proteins in patients with stroke, opposed to EVs (n = 6) and plasma (n = 5). In contrast, EVs contained most differentially-expressed proteins for MACE (n = 21) compared to plasma (n = 9) and plaque (n = 1). EVs appear to provide additional information about severity and progression of systemic atherosclerosis than can be obtained from plasma or atherosclerotic plaque.